The Relationship of Dementia and Diabetes - Tugrak Sakarya, Mehtap (Current Research in Pharmacy and Pharmaceutical Sciences II-2024, 2024)
Hypoglycemia, a common side effect of diabetes treatment, is associated with high morbidity and death, and it has become a significant barrier to the delivery of antidiabetic medication. Severe hypoglycemia, or abnormally low blood sugar, is linked to seizures and comas, but even mild hypoglycemia can induce uncomfortable symptoms including anxiety, palpitations, and confusion.Dementia frequently results in the loss of memory, language, problem solving, and other cognitive abilities that might interfere with daily activities. There is growing evidence that diabetes is linked to an increased risk of both vascular and non-vascular dementia. Neuroglycopenia caused by a hypoglycemia period in diabetic patients can result in brain cell destruction and cognitive impairment, ultimately leading to dementia. In light of new evidence, a better understanding of the relationship between hypoglycemia and dementia may help inform and guide preventive strategies. This review aims to discuss the epidemiology of dementia in patients with diabetes and the emerging mechanisms thought to underlie the relationship between hypoglycemia and dementia.